Biogenic silica-based microparticles obtained as a sub-product of the nanocellulose extraction process from pineapple peels - Corrales Ureña, Yendry R. (2018)
The nanocellulose extraction process from pineapple peels was previously described by the authors, and a diagram of the process is shown in Supplementary Fig. S1. Briefy, the ground pineapple peels were incubated in NaOH to remove the lignin and hemicellulose, then bleached in NaClO, before incubating in HCl to hydrolyze the cellulose and to obtain microcellulose. Between each step, the product was thoroughly rinsed with water until neutral pH, and the solid was recovered by centrifugation at 13000 rpm. In the final step, the material was hydrolyzed with H2SO4 to obtain NCC. Two fractions of particles were separated from this acid solution by centrifugation at 2500 rpm; the supernatant containing mainly particles in the nanometer range and the precipitate containing the micrometer solid fraction and insoluble materials. The precipitate was mainly BRMS. To purify the BRMS of cutin and NCC residues as well as remove the carbon-based materials surrounding the particles, the solid was incubated with a second H2SO4 solution. Sulfuric acid solutions of 65, 30, 15 and 2 wt.% were tested between 30 minutes and 4 hours at 55 °C (1 g of precipitate/10 ml of H2SO4 solution) to determine the lowest acid concentration needed to disperse the carbon derivatives in the solution. The second H2SO4 acid step was applied to partially depolymerize the cutin bound to polysaccharides19. Finally, the product was separated from the liquid viscous phase by centrifugation at 2500 rpm and rinsed several times with deionized water. For FTIR analysis, the cutin derivatives were separated from NCC by phase separation at 13000 rpm.